Representatives or experts? Civil society organizations in the EU's external relations - Meike Rodekamp (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
It is often claimed that the participation of Civil Society Organizations (CSOs) can mitigate the democratic deficit of the European Union. This claim rests on the assumption that civil society organizations channel citizens' concerns to the European institutions, a view which is also shared by the European Commission. But whom do Brussels-based CSOs actually represent? Some have accused Brussels CSOs of being elitist and detached from their membership bases, but not much evidence has been provided by either these critics or by the CSO sympathizers. This paper contributes to filling this knowledge gap by exploring the geographical representativeness of EU CSOs and the extent to which they involve their members in organizational activities and decision-making. CSOs in European Trade Policy (ETP) and in European Security and Defence Policy (ESDP) serve as case studies. It is assumed that the different political opportunity structures in these policy fields, namely the Commission's demand for geographical representativeness and member representation in ETP and the Council's interest in CSOs' knowledge and expertise in ESDP, are also reflected in the organizational structures of CSOs. The results confirm this hypothesis with regard to the geographical outreach of the organizations interviewed, but not with regard to the ways CSOs involve their members. CSOs in External Trade Policy have member organizations in a large number of European countries while many CSOs in ESDP lack a membership base. However, the member-based organizations of both policy fields involve their members in strategic decision-making and in diverse organizational activities and they communicate frequently with them. Evidence for a detachment of CSO secretariats in Brussels from their membership bases is scarce in the CSOs subject to this study. – – In der akademischen Debatte wird vielfach die Behauptung geäußert, die Partizipation zivilgesellschaftlicher Organisationen (ZGOs) könne das demokratische Defizit der Europäischen Union abmildern. Dem liegt die Annahme zugrunde, dass ZGOs Bürgerinteressen zu den Europäischen Institutionen kanalisieren, - eine Ansicht, die auch von der Europäischen Kommission geteilt wird. Aber wen repräsentieren die bei der EU aktiven ZGOs eigentlich? Brüsseler ZGOs stehen in der Kritik, elitär zu sein und sich von der Basis ihrer Mitglieder in den EU-Staaten entfernt zu haben. Bisher gibt es jedoch kaum empirische Untersuchungen, die die These der ZGO-Kritiker oder die der Sympathisanten stützen würden. Dieses Arbeitspapier trägt zur Schließung dieser Lücke bei, indem es die geografische Repräsentativität von Brüsseler ZGOs untersucht sowie das Ausmaß der Mitgliederpartizipation in Entscheidungsprozessen und organisatorischen Aktivitäten. Als Fallstudien dienen ZGOs in der Europäischen Außenhandelspolitik und in der Sicherheits- und Verteidigungspolitik. Es wird angenommen, dass sich die unterschiedlichen institutionellen Anreize in diesen Bereichen auch auf die interne Struktur von ZGOs auswirken: Im Bereich des Außenhandels ist der Hauptansprechpartner die Kommission, die zur Legitimation ihrer Politiken ZGOs geografische Repräsentativität und Mitgliederrepräsentation abverlangt. In der Sicherheitspolitik hingegen ist der Rat der EU die Schlüsselinstitution. Er konsultiert ZGOs vor allem aufgrund ihrer Expertise.Die Ergebnisse bestätigen die Vermutung, dass ZGOs im Außenhandel in einer größeren Anzahl von europäischen Staaten vertreten und damit geografisch repräsentativer sind. Vielen ZGOs in der Sicherheitspolitik fehlt dagegen jegliche Mitgliederbasis. Was jedoch die Mitgliederpartizipation angeht, so involvieren mitgliedsbasierte ZGOs in beiden Politikfeldern ihre Mitglieder regelmäßig und intensiv. Daher findet diese Studie nur spärliche Belege für eine Distanzierung der Brüsseler ZGOs von ihrer nationalen Mitgliederbasis.
Keywords: 330